(untitled) (Journal of Advanced Research in Social Sciences, 2025)
Born in 1907 in Istanbul, Boratav’s journey into the realm of folklore studies began at an early age, as he was deeply fascinated by the cultural narratives, customs, and beliefs that permeated Turkish society. After completing his education in Turkey, he went on to pursue further studies in France, where he earned his doctorate in Slavic linguistics from the Sorbonne University in 1933. Pertev Naili Boratav was a renowned Turkish folklorist, anthropologist, and linguist who made significant contributions to the study of Turkish culture, traditions, and oral literature. His extensive research, publications, and efforts to preserve and analyze Turkish folklore have had a profound impact on the academic landscape of Turkey and beyond. Boratav’s work spanned a wide range of topics, from the collection and analysis of folktales, proverbs, and myths to the examination of cultural practices and belief systems. He played a crucial role in the establishment of the Department of Folklore at Ankara University and mentored countless students, inspiring them to continue the legacy of preserving and disseminating Turkey’s rich cultural heritage. Given Boratav’s significant contributions to the study of Turkish anthropology and folklore, is he recognized as a pioneering anthropologist in Turkey?